Update on Ocular Myasthenia Gravis - O'Hare, Meabh; Doughty, Christopher (Seminars in Neurology, 2019)
Myasthenia gravis is an antibody-mediated autoimmune disorder of the post-synaptic neuromuscular junction resulting in fluctuating, fatigable weakness. Most patients first present with extraocular symptoms (diplopia and/or ptosis), and in 15% of cases symptoms will remain restricted to only the extraocular muscles (ocular myasthenia gravis [OMG]). The history and clinical examination are of the utmost importance in correctly identifying OMG patients, as supportive serologic or electrodiagnostic studies are frequently nondiagnostic. In this review, we outline a diagnostic approach to OMG (focusing on key clinical features), discuss therapeutic options, and highlight recent developments in the understanding of OMG.
Keywords: ocular myasthenia gravis; ptosis; diplopia; neuromuscular junction; acetylcholine receptor antibody